Current techniques to accurately measure anti-retinal autoantibodies. (3rd March 2020) - Adamus, Grazyna
ABSTRACT: Introduction : Autoimmune retinopathy (AR) is a sight-threating retinal disorder that is mediated by autoantibodies (AAbs) against retinal proteins. The visual paraneoplastic syndromes, including cancer-associated retinopathy (CAR) and melanoma-associated retinopathy (MAR), are mediated by anti-retinal AAbs. A number of immunochemical techniques have been used to detect serum anti-retinal autoantibodies in patients to help with autoimmune diagnosis. Area covered : We review techniques used for serum autoantibody evaluation in patients with suspected autoimmune retinopathy. Expert opinion : Detection of serum AAbs has served as the standard diagnostic tool for autoimmune retinopathies and for management of retinal disorders. An identification of anti-retinal autoantibody or multiple autoantibodies can be useful for not only for diagnosis of autoimmune retinopathies but also for management of retinal disorders. We propose that the line-blotting technique used in conjunction with immunohistochemistry are the best and most reliable assays for detection of serum anti-retinal AAb in the context of clinical history and findings. Clinician should recognize that the majority of antigenic targets identified to date in retinal autoimmunity are ubiquitously expressed proteins (e.g. enolase), which may be difficult to reconcile with the specific patterns of retinal damage observed in CAR, MAR, or AR.